Risk-Relevance of Fair-Value Income Measures for Commercial Banks - Hodder, Leslie D.; Hopkins, Patrick E.; Wahlen, James M. (The Accounting Review, 2006)
We investigate the risk relevance of the standard deviation of three performance measures: net income, comprehensive income, and a constructed measure of full-fair-value income for a sample of 202 U.S. commercial banks from 1996 to 2004. We find that, for the average sample bank, the volatility of full-fair-value income is more than three times that of comprehensive income and more than five times that of net income. We find that the incremental volatility in full-fair-value income (beyond the volatility of net income and comprehensive income) is positively related to marketmodel beta, the standard deviation in stock returns, and long-term interest-rate beta. Further, we predict and find that the incremental volatility in full-fair-value income (1) negatively moderates the relation between abnormal earnings and banks' share prices and (2) positively affects the expected return implicit in bank share prices. Our findings suggest full-fair-value income volatility reflects elements of risk that are not captured by volatility in net income or comprehensive income, and relates more closely to capital-market pricing of that risk than either net-income volatility or comprehensiveincome volatility.